Assessing and improving on-farm biosecurity knowledge and practices among swine producers and veterinarians through online surveys and an educational website in Illinois, United States - Agrawal, Isha; Bromfield, Corinne; Varga, Csaba (Frontiers in Veterinary Science, 2023)
There is a growing risk to the health and productivity of the Illinois and United States swine population from foreign and endemic infectious diseases. Effective on-farm biosecurity practices play a pivotal role in preventing these high-consequence pathogens from affecting swine farms. Veterinarians are essential in providing disease prevention advice to swine producers that can help them implement effective biosecurity practices on their farms. Our descriptive study objectives were to assess Illinois swine producers’ and veterinarians’ biosecurity perception, knowledge, and practices to identify knowledge gaps and address these by developing an online educational website. We developed two independent online questionnaires using QualtricsXM software. Swine producer members of the Illinois Pork Producers Association and veterinarians registered with the Illinois State Veterinary Medical Association were contacted via e-mail through their associations and asked to complete an online survey. In total, 13 swine producers across 9 Illinois counties operating 82 farms (8 managed single farms and 5 managed multiple farms) responded to the swine producer survey. Despite some biosecurity awareness among swine producers, the need for a biosecurity-related outreach program was evident. Among the 7 swine veterinarian responders, 5 predominantly treated swine (oversaw an average of 21.6 farms), and 2 were mixed animal practitioners. The swine veterinarian survey showed a disconnect between their biosecurity perception and practices. We developed a biosecurity educational website and used Google Analytics to collect website traffic and user data. The 4 months of data showed good coverage that included the highest proportion of users from the Midwest and North Carolina, the largest swine-production regions in the US, and China and Canada, the leading producers of swine worldwide. The most accessed webpage was the resources page, and the swine diseases page had the highest engagement time. Our study highlights the effectiveness of combining online surveys with an educational website to assess and improve the biosecurity knowledge of swine producers and veterinarians that can be applied to assess and improve the biosecurity knowledge and practices of other livestock farmers.